(3MGTjI Ydi TQM edNU GdLZejfi dbGVi RGOI GdQheis - (3SfGf GdOjf jhSa Hf NVQ (B( (3NjQ GdOjf (B) (3Hf LdGd GdOjf GdQhej GdMfaj, SfGf HGTG , NhLg HGTG,J (B891 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi UhQ gjFI GdYGde GdfGXQ HYjf Gddg Edi eG ai JQJjH YGde GdSehGJ ef YLGFH GdChVGY hdjS dfG Yde jYjf Ydi gPG GdJacQ ZjQYde GdgjFI heSGFdgG s
(3BNQgG (B:s
(3ajchf eG PcQ eLQO aQV hJbOjQ deMGd hdG MGLI Edjg eY XghQ GdOQLI GdChdi , hEf cGf cdG GdhLgjf ef fJGFL NGWQi GdaGJQ ESJNQLJgeG HYhf Gddg JYGdi Je gPG GdcJGH s
(3HgG CTcGd HChdgG JedcGJ ZjQ eDQNIs
(3cJHgG HETGQI GdSdWGf eMeO Hf eQGOs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B9 - (3U (B228 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B158 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B562s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B327 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1819s
Keywords: (3Gdadcs